Perceptions Surrounding the Role of Recreational Therapy within Transitions Services as a Pathway to Employment for Individuals with Intellectual and Developmental Disabilities - Clatfelter, Alexa (East Carolina University)
The current rate of employment in the US for ages 16 and over is 60.2% (US Department of Labor, 2024); however, individuals with intellectual and developmental disabilities (IDD) are underemployed. In comparison, the employment rate for individuals with IDD in the United States is 34%, with only 18% holding a competitive job (Avellon et al., 2021). In K-12, students with disabilities including IDD are eligible and required to receive a free and appropriate education deemed necessary under the Individuals with Disabilities Education Act (IDEA). This includes transition services starting at the age of 16 focusing on functional skills for work and community life (US Department of Education, 2017). Recreational therapy (RT) as a related service to education, special education, and transition services is included under IDEA; however, RT is not prevalent within schools nor transition services. Nevertheless, one of recreational therapy’s mandates is to facilitate skills and opportunities for community life for their clients with disabilities. Therefore, this study aimed to gauge the perceptions of RT within transition services as a pathway to employment for individuals with IDD through a grounded theory approach of qualitative research. The study primarily focused on a community located in the eastern region of NC as the population of individuals with IDD in NC (18%) (NCDHHS, 2023) is noted to be higher than the national average of approximately 3% (US Census, 2019). Data collection included interviews with individuals with IDD, their parents/ family, and/or caregivers, employers, recreational therapists, and those working within related disciplines. Data analysis used the method of constant comparison of emerging codes and axial codes where utilization of two additional reviewers on the research team triangulated the data for credibility and trustworthiness. Five themes were constructed from patterns of similarities and differences from transcribed interviews. The findings of this study included the societal perceptions of individuals with IDD, their characteristics in the workplace, and what is needed for them to achieve employment and maintain it. This study also has multiple implications for both practitioners and future research, including the underutilization of recreational therapy services as a pathway of employment for individuals with IDD and types of settings for such employment.
Keywords: Recreation